Ferroptosis in Neurological Diseases - Ren, Jia-Xin; Sun, Xin; Yan, Xiu-Li; Guo, Zhen-Ni; Yang, Yi (Frontiers in Cellular Neuroscience, 2020)
Ferroptosis is mechanism for non-apoptotic, iron-dependent, oxidative cell death that is characterized by glutathione consumption and lipid peroxides accumulation. Ferroptosis is crucially involved in neurological diseases, including neurodegeneration, stroke and neurotrauma. This review provides detailed discussions of the ferroptosis mechanisms in these neurological diseases. Moreover, it summarizes recent drugs that target ferroptosis for neurological disease treatment. Furthermore, it compares the differences and relationships among the various cell death mechanisms involved in neurological diseases. Elucidating the ferroptosis role in the brain can improve the understanding of neurological disease mechanism and provide potential prevention and treatment interventions for acute and chronic neurological diseases.